A G protein-coupled receptor, groom-of-PDF, is required for PDF neuron action in circadian behavior. - Lear, B.C.; Merrill, C.E.; Lin, J.M.; Schroeder, A.; Zhang, L.; Allada, R. (Neuron, 2005)
The neuropeptide Pigment-Dispersing Factor (PDF) plays a critical role in mediating circadian control of behavior in Drosophila. Here we identify mutants (groom-of-PDF; gop) that display phase-advanced evening activity and poor free-running rhythmicity, phenocopying pdf mutants. In gop mutants, a spontaneous retrotransposon disrupts a coding exon of a G protein-coupled receptor, CG13758. Disruption of the receptor is accompanied by phase-advanced oscillations of the core clock protein PERIOD. Moreover, effects on circadian timing induced by perturbation of PDF neurons require gop. Yet PDF oscillations themselves remain robust in gop mutants, suggesting that GOP acts downstream of PDF. gop is expressed most strongly in the dorsal brain in regions that lie in proximity to PDF-containing nerve terminals. Taken together, these studies implicate GOP as a PDF receptor in Drosophila.